The Effects of TikTok Videos in Flipped Learning on Vocabulary Achievement and Learning Engagement - Louise Valentyna (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Vocabulary mastery is an important aspect of English learning, particularly for vocational high school students who need English to support their future careers. However, many students still experience difficulties in learning vocabulary. Therefore, this study investigated the effect of teacher-created TikTok videos integrated with a flipped learning approach on students’ vocabulary achievement and learning engagement. This study employed a quasi-experimental design involving two intact classes of eleventh-grade Accounting students at a vocational high school in Jember, East Java. The experimental group learned through teacher-created TikTok videos in flipped learning, while the control group received conventional instruction. Data were collected through vocabulary tests and learning engagement questionnaires and analyzed using SPSS. The findings revealed that the experimental group showed a significant improvement in vocabulary achievement and learning engagement compared to the control group. The post-test and post-questionnaire results indicated significant differences between the two groups (p = 0.000). It can be concluded that teacher-created TikTok videos integrated with flipped learning are effective in improving vocational high school students’ vocabulary achievement and learning engagement.
Finalisasi 21 Juli 2026_Yudi
Keywords: TikTok Videos; Flipped Learning; Vocabulary Achievement; Learning Engagement; English as a Foreign Language; ESP Programs